Activist Distressed Debtholders: The New Barbarians at the Gate? - Michelle M. Harner (Washington University Law Review, 2011)
The term “corporate raiders” previously struck fear in the hearts of corporate boards and management teams. It generally refers to investors who target undervalued, cash-flush or mismanaged companies and initiate a hostile takeover of the company. Corporate raiders earned their name in part because of their focus on value extraction, which could entail dismantling a company and selling off its crown jewels. Today, the term often conjures up images of Michael Milken, Henry Kravis, or the movie character Gordon Gekko, but the alleged threat posed to companies by corporate raiders is less prevalent—at least with respect to the traditional use of equity to facilitate a hostile takeover. The growing use of debt rather than equity to cause a change of control at target companies raises new concerns for corporate boards and management teams and new policy considerations for commentators and legislators. Are activist debtholders who employ this investment strategy akin to the corporate raiders of the past? This Article explores these issues by, among other things, presenting in-depth case studies and critically evaluating the value implications of traditional takeover activity and regulation. It compares and contrasts the use of equity and debt in control contests and identifies similarities that suggest some regulation of strategic debt acquisitions is warranted. The Article proposes a proactive approach that better equips corporate boards and management teams to negotiate with activist debtholders while preserving investment opportunities for debtholders and the governance efficiencies that often flow from activism for the corporate target‟s other stakeholders.
Keywords: Distressed debt; Hostile takeovers; Williams Act; United States